TRANSAKSI JUAL BELI ITEM VIRTUAL DALAM GAME ONLINE DENGAN SISTEM GACHA PERSPEKTIF FIQH MUAMALAH - M.H, Muspitasari; Setiawan, Ageil; Djabbar, Yusuf (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2025)
This article examines the legal standing of buying and selling virtual items in online games that use the Gacha system, which often involves loss and uncertainty (Gharar). The Gacha system in online games typically begins when a player, acting as the buyer, performs a top-up to purchase items (in-game currency exchange) from a top-up provider acting as the seller. The virtual goods obtained are then exchanged for Gacha tickets; however, during this process, buyers are not guaranteed to receive the items they desire. Instead, they receive items based on predetermined probability rates outlined in the game's terms. Players require in-game currency to spin or draw from the Gacha in order to use this method. Essentially, a contract must be based on mutual consent of the parties involved, but this method introduces various levels of uncertainty into the transaction. The use of the Gacha system in online games for buying and selling is prohibited in Islamic commercial jurisprudence (fiqh muamalah) because it violates one of the essential pillars and conditions of a valid sale—namely, that the item received does not match what was intended or expected. This means the transaction contains elements of gharar, which is prohibited in Islam and renders the sale invalid under fiqh muamalah.